Mabel Dodge Luhan : new woman, new worlds - Rudnick, Lois Palken, 1944-2021. (Albuquerque : University of New Mexico Press, 1984)
This fascinating biography reveals a complex and talented woman who tried to influence the course of American history and in so doing captured the imaginations of writers and artists seeking to come to terms with their visions of the twentieth century. Luhan's life is the story of America's emergence from the Victorian age, and, in particular, the story of the conflicts that American women experienced in their struggle to become movers and shakers. Both as a woman and as a legend, Mabel Dodge Luhan embodies the cultural forces that have shaped modern America. - Back cover.
Background (1879-1905) -- European experiences (1905-1912) -- Movers and shakers (1912-1915) -- Art, nature, and mind-cure (1915-1917) -- Edge of Taos Desert (1917-1926) -- Sybil, the Phoenix, and the queen bee : the Luhans and the Lawrences -- The other side of paradise (1926-1929) -- Intimate memories (1930-1940) -- Epilogue (1940-1962).
Includes index.
Bibliography: p. 362-370.
Keywords: Luhan, Mabel Dodge, -- 1879-1962.; United States -- Biography